(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article discusses various strategies to improve audience engagement in presentations by incorporating interactive methods. It emphasizes the shift from traditional passive listening to active participation, highlighting the benefits of audience involvement for better content retention, deeper understanding, and stronger connections. Key methods explored include polls and surveys, Q&A sessions, interactive storytelling, gamification, collaborative exercises, and the use of technology such as augmented reality (AR) and virtual reality (VR). The article underscores the importance of creating an engaging, dynamic experience for the audience, and stresses that interactive techniques not only enhance learning but also foster creativity, participation, and meaningful exchanges between the presenter and audience. By leveraging these strategies, presenters can transform their sessions into memorable and impactful events, ensuring their message resonates beyond the presentation itself.